URGENSI PENDIDIKAN SABAR DALAM KISAH NABI YUSUF AS - Mukimin, Nurlaela Noviatun Khoiriah; Sunarko, Asep; Al-Adib, Muhammad Najib (Al Jabiri: Jurnal Ilmiah Studi Islam, 2023)
This research aims to determine the importance of patient education in the story of the Prophet Yusuf contained in Surah Yusuf. This research includes library research with a qualitative approach, namely by using several pieces of literature as research objects. The data collection technique is in the form of documentation, by collecting information from various data sources. Meanwhile, data analysis uses the maudhu'i method, content analysis and discourse analysis methods. The results obtained from this research show that the importance of patient education is carried out because it can influence the motivation of teachers and students in the learning process. There are several points related to the importance of patient education contained in Q.S Yusuf in the context of education, including: Acting fairly and not being selective towards students, Educating and teaching science with patience, Patience in undergoing the learning process, Patience is an education about self-control, strengthening students' moral values ​​and character, strengthening the value of honesty and applying the Story of the Prophet Yusuf as a story method in learning at school.